Partnership for scaling up Climate-Smart Agriculture (P4S) - Project flyer - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
P4S seeks to address gaps in data availability and adequacy for decision-making. Many agricultural management options are available, leading to an equally rich set of possible outcomes. For project planners, investors and policy makers, this creates challenges in identifying—in a cost- and time-effective manner—what will work where and the costs associated. Moreover, scientific data is usually published in outlets that require long processes before the information can be used in decision-making (traditionally low journal review speed). The research then gets filed—oftentimes behind firewalls— and unavailable for use by non-technical audiences.